Respuesta :
Let's solve your equation step-by-step.
3m+1m−7+3m=21
Step 1: Simplify both sides of the equation.
3m+1m−7+3m=21
Simplify: (Show steps)
7m−7=21
Step 2: Add 7 to both sides.
7m−7+7=21+7
7m=28
Step 3: Divide both sides by 7.
7m/7=28/7
m=4
Answer:m=4
3m+1m−7+3m=21
Step 1: Simplify both sides of the equation.
3m+1m−7+3m=21
Simplify: (Show steps)
7m−7=21
Step 2: Add 7 to both sides.
7m−7+7=21+7
7m=28
Step 3: Divide both sides by 7.
7m/7=28/7
m=4
Answer:m=4
3m + 1m -7 + 3m = 21
3m + 1m -7 + 3m = 21
+7 + 7
3m + 1m +3m =28
7m =28
7m/7 =28/7
m=4
3m + 1m -7 + 3m = 21
+7 + 7
3m + 1m +3m =28
7m =28
7m/7 =28/7
m=4